PHYSIOCHEMICAL AND PARTIAL PURIFICATION OF CRUDE ALKALOID COMPOUNDS IN BERRIES, LEAVES AND ROOTS OF ( Solanum nigrum) PLANTS. - Mohammed, Ali; Al-Dulami, Mohammed; Saour, Kawkab (Iraqi Journal of Science, 2024)
This study included extraction, physiochemical and partial purification of some crud alkaloide compounds in berries, leaves and roots of (Solanum nigrum) Solanaceae plants, which is locally named ( ANAB Al-THEA’B ) . It’s the most important medicinal herb, which is widely distribution in IRAQ and used in folklore medicine. The phytochemical investigation of the plant was designed to evaluate alkaloid contente in berries, leaves and roots. Four major crud alkaloid were isolated and partially purified as follows, ( a, b, c and d ). The yield was 8.73%, 9.5%, 0.9% and 0.33% respectively. Acid hydrolysis was performed using limited concentration of HCl or H2SO4 to obtain the aglycon part of the previously separated component as ( A, B, C and D ), the yield was 5.5%, 6.5%, 0.8 % , 0.3% respectively. The content of the active biological compounds such as (alkaloids, glycosides, saponins, coumarins, tannins and resins) was mainly showed in berries and leaves, but low in the roots, in which the detection of glycosides was negative.